The Efficiency of Art-Based Interventions in Parental Training - Shamri Zeevi, Liat; Regev, Dafna; Guttmann, Joseph (Frontiers in Psychology, 2018)
In recent years, the field of art therapy has gained momentum, but art therapists still tend to work verbally during sessions with parents. The therapeutic approach presented here is anchored in the notion that the encounter between the art world and treatment creates a unique relationship between therapist, parents and the artwork. Eighty-seven parents of five to eight year olds filled in two quantitative questionnaires before and after a ten-month therapeutic intervention during which their child was treated through art therapy. Two other questionnaires were completed by the children and by the 14 art therapists. Three groups were tested: 1. Parental training with art-based interventions (intervention group). 2. Verbal parental training. 3. No Parental training. The parents in the first and second groups met the art therapist for parental training once every three to four weeks. In the intervention group the art intervention was based on a uniform protocol of exercises with various materials. It was hypothesized that a combination of art-based interventions during parental training (parents whose child was receiving art therapy) would contribute more to parent-child relationship, affect the parents' self-perceptions of parental functioning, and improve the child's daily functioning than verbal parental training or no parental training, both in terms of the parents' and the child’s perception. Analysis of the children's questionnaire indicated significantly higher scores in the intervention group than in the control groups for perceived cognitive abilities, perceived acceptance by peers and by the mother. Analysis of the parents' questionnaires indicated there was no difference in parental perceptions of their child, level of satisfaction, or efficiency between the intervention and the control groups. The art therapists reported improvement in the intervention group on almost every measure. When parents take part in a therapeutic experience that enables them to create and play with art materials, they may accept and appreciate their inner 'child' more easily. This may help them accept the fact that their own children are dependent on them, while at the same time acknowledging their need for autonomy, which can heighten children's perception of their own acceptance by peers and acceptance by their parents.